Corneal Involvement in HIV-infected Individuals. (18th August 2021) - Radhakrishnan, Naveen; Smit, Derrick; Venkatesh Prajna, N; S.R., Rathinam
ABSTRACT: Corneal involvement in HIV-infected individuals may be broadly classified into two categories, namely, infectious and noninfectious with the vast majority of manifestations occurring in the former. In this article, we shall focus on these two categories and strive to highlight those presentations that should alert the clinician to suspect underlying HIV infection. Infectious group mainly consists of Herpitic group of viral infections. Bacterial causes may be due to Staphylococcus epidermidis, Staphylococcus aureus, Pseudomonas aeroginosa, alpha hemolytic Streptococcus, Micrococcus and Bacillus . Fungalf keratitis in HIV-infected individuals depends on the geographic locations from which patient comes. Microsporidia and Acanthamoeba are common Protozoal causes. Non-infective inflammatory causes include peripheral ulcerative keratitis, keratoconjunctivitis sicca, and squamous cell carcinoma of the conjunctiva. Severity which is abnormally severe or very minimally reactive makes the clinician suspect of immunosuppression.